Using Transcranial Alternating Current Stimulation (tACS) to Improve Romantic Relationships Can Be a Promising Approach - Liu, Shen; Ma, Ru; Liu, Xiaoming; Zhang, Chong; Chen, Yijun; Jin, Chenggong; Wang, Hangwei; Cui, Jiangtian; Zhang, Xiaochu (Frontiers in Psychology, 2019)
The romantic relationship refers to the specific relationship in which partners are dependent upon each other to obtain satisfactory outcomes and facilitate the pursuit of their most important needs and goals. Satisfying romantic relationships is a strong predictor of better psychological well-being, better physical health, and longer life expectancy. However, romantic relationships are not all smooth-sailing and lovers are often confronted with a variety of unavoidable issues that constantly challenge the stability of their romantic relationships. Dissatisfying romantic relationships are harmful and even destructive. Dyads of lovers engage in a variety of efforts to protect and maintain their romantic relationships based on qualitative research methods including theories- and psychological consultation-based approaches. Unfortunately, those existing approaches do not seem to effectively improve romantic relationships. Thus, it is necessary to seek an efficient approach regulating dyads of lovers in romantic relationships simultaneously. Transcranial alternating current stimulation with advantages over existing approaches satisfies this purpose. We discuss the practicability of tACS in detail, as well as why and how tACS can be utilized to improve romantic relationships. In summary, this review firstly introduced the concept of romantic relationship and the necessity of enhancing it. Then, it discussed methods to improve romantic relationships including some existing approaches. This review next discussed the practicability of using transcranial alternating current stimulation to improve romantic relationships. Finally, it shone a spotlight on potential future directions for researches aiming to improve romantic relationships.